2014
DOI: 10.1007/s11250-014-0622-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding cassava (Manihot esculenta Crantz) root meal on growth performance, hydrocyanide intake and haematological parameters of broiler chicks

Abstract: The effect of feeding cassava root meal on growth performance, hydrocyanide intake, haematological indices and serum thiocyanate concentration of broiler chicks was investigated using 300-day-old male broilers. There were five dietary treatments arranged in a 2 × 2 + 1 factorial arrangement of two processing methods of cassava root (peeled and unpeeled) included at two levels (100 and 200 g/kg) plus a control diet (maize-based diet, containing no cassava root). Each treatment was replicated six times with ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
0
11
2
Order By: Relevance
“…This present finding was different from that of reported by Akapo et al (2014) when feeding 10 % peeled cassava root meal, resulting in reduced final BW and increased feed-to-gain ratio of broilers. The increased dietary crude fibre and HCN and the reduced CP contents with increasing the levels of cassava root had been suggested to predispose the cassava-fed birds to gain less weight as compared to control (Akapo et al 2014). This seemed, however, not the case in our present study as we balanced the energy, CP and fibre contents in our experimental diets.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This present finding was different from that of reported by Akapo et al (2014) when feeding 10 % peeled cassava root meal, resulting in reduced final BW and increased feed-to-gain ratio of broilers. The increased dietary crude fibre and HCN and the reduced CP contents with increasing the levels of cassava root had been suggested to predispose the cassava-fed birds to gain less weight as compared to control (Akapo et al 2014). This seemed, however, not the case in our present study as we balanced the energy, CP and fibre contents in our experimental diets.…”
Section: Discussioncontrasting
confidence: 99%
“…the content of cyanogenetic glycosides compounds (Chauynarong et al 2009). Akapo et al (2014) reported that although inclusion of 10 % peeled cassava root meal in the diet had some economic advantages, this practice might impair the growth and health of broiler chickens due to reduced protein content and the presence of cyanogenetic glycosides residues leading to incidence of toxicity. Earlier study has confirmed that fermentation could be a simple means to detoxify cyanogenetic glycosides in cassava roots (Kobawila et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In a study with local chickens [40], it was reported that birds lost 2 g/day when feed fresh feed materials, including cassava roots and duckweed, and attributed the poor performance mostly to the presence of ANF in the fresh feed materials. When unprocessed (peeled and unpeeled cassava root meal) was fed to broilers, Akapo et al [41] reported depressed feed intake, weight gain and feed-to-gain ratio, mostly with birds fed the unpeeled cassava root meal. The study concluded that up to 100 g/kg dietary inclusion of the meals poses a threat to growth and health status of broiler chicks [41].…”
Section: Effect Of Feeding Raw/unprocessed Cassava To Poultrymentioning
confidence: 99%
“…When unprocessed (peeled and unpeeled cassava root meal) was fed to broilers, Akapo et al [41] reported depressed feed intake, weight gain and feed-to-gain ratio, mostly with birds fed the unpeeled cassava root meal. The study concluded that up to 100 g/kg dietary inclusion of the meals poses a threat to growth and health status of broiler chicks [41].…”
Section: Effect Of Feeding Raw/unprocessed Cassava To Poultrymentioning
confidence: 99%
“…Linamarin is cyanogenic glycosides (2-B-Dglucopyranosy 1oxy-isobutryo nitrite) found in leaves and tuberous roots of cassava, which release high toxic cyanide (HCN) during hydrolysis at the time of digestion (Presston, 2004;Aderemi et al, 2012;Akapo et al, 2014). Previous researchers have attempted to increase non-conventional plant and animal materials to replace conventional feed ingredients like maize and fish meal in fish feed ration (Falaye, 1988;Fagbenro, 1992;Olatunde, 1996;Baruah et al, 2003;Eyo and Ezechie, 2004;Azaza et al, 2015).…”
Section: Introductionmentioning
confidence: 99%